Effectiveness of Geogebra in Learning Matrices - Acharya , Megh Raj (Butwal Campus Journal, 2025)
Learning mathematics becomes easier through the use of geogebra. In the learning process student need technology This study was conducted using a quasi- experimental design. Through the quasi experimental. Geogebra was found to be helpful for learning matrix. The B.Ed science students from Butwal Multiple Campus were selected based on convenience sampling. Students were divided in to two groups, an experimental group and a control group. The significance between the two groups was determined on the basic of their mean scores. The experimental group showed a better understanding of the concepts of matrix. A survey instrument, a quantitative approach was used in this study. Students achievement in matrix was measured through pre test and post test. In this study a t test was used and the p value was found to be 0.002. The analysis showed a positive perception towered matrix learning.